A life in comparative politics: Chasing questions in five continents. Issue 5 (November 2016) - Stepan, Alfred
Why, as a comparativist, did I find it compelling to carry out field research in over 20 countries on five different continents? Because comparative politics should be question-driven, not driven by methodology or existing data. Good questions led to new countries. My book on how Brazilian civilian elites were complicit in coups led to a comparative book on how to transform such civil–military relations in Brazil, Chile, Argentina, and Uruguay. My colleague Juan J Linz and I broadened the scope of questions of democratic transition theory by adding post-communist countries to the transition set. New questions and relevant new countries continue to emerge. What to do if more than one nation exists in a polity pursuing 'nation-state' policies? I helped create the concept of 'state-nation' and documented how 'multiple but complementary identities' were fostered in India. How did polities that respected the 'twin tolerations' emerge in Muslim-majority Indonesia, Senegal, and Tunisia?